2011
DOI: 10.1021/nl2033602
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nanostructures as Highly Efficient Generators of Second Harmonic Light

Abstract: Plasmonic nanostructures enable the generation of large electromagnetic fields confined to small volumes, potentially providing a route for the development of nanoengineered nonlinear optical media. A metal-capped hemispherical nanoparticle, also known as a nanocup, generates second harmonic light with increasing intensity as the angle between the incident fundamental beam and the nanocup symmetry axis is increased. Nanoparticle orientation also modifies the emission direction of the second harmonic light. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
271
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(289 citation statements)
references
References 34 publications
12
271
0
2
Order By: Relevance
“…It has recently been shown that certain plasmonic nanostructures can produce an enhanced nonlinear response when excited at their resonant frequency (1,2). Phase-matching requirements (3)(4)(5) for nonlinear optics in macroscopic media are usually optimally fulfilled at nanoscale dimensions [sinc 2 (Δk z/2) ∼1 for small z, where z is the propagation distance through the medium]. For plasmonic nanostructures, the most important property for the enhancement of nonlinear properties is their increased local fields at resonance, which can provide larger effective susceptibilities than their intrinsic material susceptibility.…”
mentioning
confidence: 99%
“…It has recently been shown that certain plasmonic nanostructures can produce an enhanced nonlinear response when excited at their resonant frequency (1,2). Phase-matching requirements (3)(4)(5) for nonlinear optics in macroscopic media are usually optimally fulfilled at nanoscale dimensions [sinc 2 (Δk z/2) ∼1 for small z, where z is the propagation distance through the medium]. For plasmonic nanostructures, the most important property for the enhancement of nonlinear properties is their increased local fields at resonance, which can provide larger effective susceptibilities than their intrinsic material susceptibility.…”
mentioning
confidence: 99%
“…The localized surface plasmon resonance enhances efficiency and can be designed by selecting the nanoparticle shape for a given wavelength; selective polarization response can also be designed into the nanoparticle. A number of asymmetric plasmonic geometries have been used for harmonic generation, including L-and V-shaped nanoparticles, nanocups, and asymmetric trimers [3][4][5][6][7]. Larger plasmonic structures-such as the ratchet wheel-have also been shown to affect the polarization of harmonic emission [8][9][10][11][12].…”
mentioning
confidence: 99%
“…These characteristics make the nanospiral a strong candidate for nonlinear optical applications where a broadband plasmonic element is necessary. Unlike plasmonic structures with globally broken symmetry created by modifying or arranging nanoparticles with some inherent local symmetry, [3,4,7,14] the nanospiral has no local axis of symmetry at all so that the nanospiral can generate secondharmonic light from any polarization state. This inherent lack of symmetry therefore makes the nanospiral an attractive candidate for nonlinear metasurface elements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, advances of nanofabrication techniques [7,8] have enabled control of the sizes, shapes, and alignment of nanostructures of a wide range of materials, and their SHG responses have been investigated. For example, the reports for SHG responses from the GaAs nanoneedles grown by the chemical vapor deposition method [9], the nanocups deposited Au by electron-beam evaporation on to silica nanoparticles [10], the ZnO nanorods grown on glass substrates by means of the low-temperature chemical bath method [11], the Pt nanowires created by the physical vapor deposition method [12], and the Au nanoholes fabricated by the focused ion beam method [13] attracted most researchers. These SHG processes are used in a wide range of applications, such as developing devices for optical processing [14], nonlinear imaging [4], and phase-sensitive amplification [15].…”
Section: Introductionmentioning
confidence: 99%